INTERACTIVE ANIMATION TO INCREASE THE STUDENTS' READING COMPREHENSION - Reka Mardiana; Aswadi Jaya; Ana Theriana (Esteem Journal of English Education Study Programme, 2023)
The aim of this study was to examine the effects and advantages experienced by teachers and students when utilizing interactive animation. The research problem in this study focused on the perceptions of teachers and students regarding the impact of interactive animation on enhancing students' abilities as well as the benefits associated with its use. The study employed a descriptive qualitative method, and data was gathered through triangulation using questionnaires, interviews, and observations. The data analysis revealed that animated videos facilitated easier comprehension of narrative texts for students. The videos effectively portrayed moving objects accompanied by sound, captivating students' attention and fostering their enthusiasm during the learning process. The students demonstrated active engagement and attentiveness to the storyline. Utilizing animated videos as a teaching tool for narrative texts was found to be an effective approach. Finally, it is essential for teachers to address the basic English skills of their students as they navigate the challenges associated with this teaching method.